(untitled) (Tábano, 2025)
For Deleuze and Guattari, art is a bomb, and the artist is a revolutionary, creating incendiary devices that explode beyond our expectations, our regulations, and our representative norms. But what is this art explosion? It is the raw force of sensation, a sensation that goes beyond the limits of our ability to represent it, something that is always new and undetermined by our physical, conscious or historical conditions. This overwhelming sensation emerges from Deleuze’s fascination with Kant’s sublime, which in a significantly altered form emerges in Difference and Repetition as the key to Deleuze’s own aesthetic, which is founded on the discord of the faculties. Deleuze’s revisionist reading of the sublime opens Kant’s system to new possibilities, ones even Kant himself was not aware of. The sublime continues to be the principle of Deleuze’s aesthetic in his later work, in particular in the Cinema books, and Logic of Sensation, Francis Bacon.